PENGEMBANGAN E-LKD BERBASIS CONTEXTUAL TEACHING AND LEARNING PADA MATERI GEOMETRI BANGUN DATAR KELAS IV SD - Siti Tiara Fatma; Allen Marga Retta; Arief Kuswidyanarko (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to produce E-LKPD based on Contextual teaching and learning onthe material of flat geometry in grade IV of elementary school that is valid, practicaland effective. The method used in this study is the research and developmentmethod, using the ADDIE model through the stages of analysis, design,development, implementation, and evaluation. Data collection using interviews,questionnaires, test results, documentation. Data analysis techniques are carriedout by analyzing validity, practicality and effectiveness. The results of dataanalysis in the E-LKPD development study obtained a validity value of 93%, with avery valid category, then obtained a practicality value of 88.6% with a verypractical category, and obtained an effectiveness value of 74% with an effectivecategory. Based on the results of the analysis of validity, practicality andeffectiveness, it can be concluded that E-LKPD based on contextual teaching andlearning is suitable for use in learning mathematics on flat geometry material ingrade IV of elementary school.